Evidence of natural interspecific recombinant viruses between bovine alphaherpesviruses 1 and 5 - Maidana, Silvina Soledad (2017)
Closely related bovine alphaherpesviruses 1 (BoHV-1) and 5 (BoHV-5) co-circulate in certain countries, rendering cattle co-infection possible. This is a prerequisite for BoHV recombination. Here, we report the first identification of homologous recombination between field isolates of BoHV-1 and BoHV-5, two alphaherpesviruses belonging to two distinct species with an average genomic similarity of 82.3%. Three isolates of BoHV-5, previously classified as subtype “BoHV-5b”, were phylogenetically studied and analyzed via eight PCR sequencing assays dispersed at regular intervals throughout the genome to discriminate between BoHV-1 andBoHV-5. In the phylogenetic analysis, differences of clustering were found in the UL27 gene which encodes the glycoprotein B (gB). We detected two recombination breakpoints in the open reading frame of the UL27 gene. We compared the amino acid sequences of the gB of BoHV-1.1 and 1.2, BoHV-5a and recombinant formerly named BoHV-5b (chimeric gB) and subsequently performed molecular modeling. All structures were alike and, simultaneously, similar to the chimeric gB. Neutralizing antibodies against BoHV-1, BoHV-5 and recombinant viruses were analyzed via serum virus neutralization test using polyclonal sera and a monoclonal antibody against gB to demonstrate an absence of viral escape for both assays. Our results show that homologous recombination between two related species of ruminant alphaherpesviruses can occur in natural field conditions. We found three recombinant field isolates, previously classified as BoHV-5b subtypes, between BoHV-1 and BoHV-5.